2023
DOI: 10.1007/s10018-023-00363-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of European municipalities and regions in financing energy upgrades in buildings

Abstract: Energy efficiency in buildings has a central role to play in reaching the climate neutrality goal set by the European Green Deal. With detailed knowledge of their building stock and the profile of their occupants, regional and local authorities can forge an important link between financiers, industry professionals and homeowners to ensure the successful deployment of financial schemes that support the uptake of energy efficiency upgrades. This paper provides a first assessment of the role of regional and local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…While we found green buildings to represent the least cost-effective projects municipalities have invested their proceeds from green bonds into, it must be acknowledged that financial schemes are in place to provide the right incentives to improve the cost-efficiency of green buildings in Europe. Previous research has found regions, municipalities and other local authorities in the EU to be in an excellent position to make the best use of the European structural and research funds to create financial schemes to enhance the process of energy reduction in the real estate sector (Economidou et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…While we found green buildings to represent the least cost-effective projects municipalities have invested their proceeds from green bonds into, it must be acknowledged that financial schemes are in place to provide the right incentives to improve the cost-efficiency of green buildings in Europe. Previous research has found regions, municipalities and other local authorities in the EU to be in an excellent position to make the best use of the European structural and research funds to create financial schemes to enhance the process of energy reduction in the real estate sector (Economidou et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The complex decision-making process for multi-family buildings not only hinders residents facing energy poverty, but creates difficulties for all. However, the specificity of energy poverty leads to specialised financial solutions (Economidou, et al, 2023). It is mainly proposed to use grants and subsidies for renovation and to use funds from energy savings.…”
Section: Renovation Rate and Energy Povertymentioning
confidence: 99%
“…collection seeks to advance our understanding of the complex challenges and opportunities inherent in fostering sustainable urban environments (Wolf et al 2022;Ben Youssef 2022;Moinse et al 2022;Economidou et al 2023).…”
mentioning
confidence: 99%